The Cape Town Violence and Injury Observatory (VIO) Validity and utility of data sources for a prevention-oriented VIO in urban Cape Town, South Africa - Jabar, Ardil (Department of Public Health and Family Medicine, 2022)
Background The Cardiff model purports that the true burden of violence within a community can only be quantified by the addition of violence-related data from health services to violence data reported to the police. This thesis describes the conceptualisation, development and implementation of a violence and injury observatory for the routine collection of violence-related data for the City of Cape Town. The observatory model, which was conceptualised in the early 1990s in Colombia, has gone through various iterations as a municipality-level research tool, to a city-level tool and thereafter as a national and transnational tool. Aims of this thesis The thesis aimed to assess the utility of clinical and non-clinical data sources in constituting a prevention-oriented violence and injury observatory (VIO) in urban Cape Town, South Africa. The specific objectives of each study component were as follows: • To describe the objectives of the pilot VIO, potential violence-related datasets for collection, data analysis and research dissemination plan (Study One) • To assess the validity and utility of VIOs in reducing violence and violencerelated harms in adult populations (Study Two) • To identify the optimal data elements for inclusion in a VIO according to expert consensus (Study Three) • To determine the concordance between violent crimes reported to the police with violence-related injuries presenting at health facilities in Khayelitsha (Study Four). Methods The systematic review method was used to determine whether the introduction of violence and injury observatories was associated with a reduction in violence in adult populations (Study Two). A modified two-round Delphi study (Study Three) determined the optimal data elements (including violence and injury indicators, datasets and research priorities) for inclusion in a pilot violence and injury observatory in Cape Town. The Delphi panel of 21 participants included one Provincial Head of Emergency Medicine, one Provincial Head of Disaster Medicine, several Heads of Department of Emergency Medicine across hospitals in Cape Town, and representatives from relevant data stakeholders, including the Forensic Pathology Services (FPS), South African Police Services (SAPS), Health Systems Trust (HST) and the Violence Prevention through Urban Upgrading (VPUU). This was to ensure that decisions were made by persons in senior posts to facilitate subsequent implementation of the recommendations. Khayelitsha, a peri-urban mixed informal township of Cape Town, was the setting for the final study (Study Four), which included a retrospective analysis of secondary cross-sectional health and police data, from three health facilities and three police stations in the community of Khayelitsha, Cape Town. A case-matching study, using personal identifier matching, was employed to determine the concordance between reports of violent crimes to police stations with reports of injuries arising from interpersonal violence at health facilities within the community of Khayelitsha in Cape Town, South Africa. Results and Discussion Subgroup analyses according to the two types of models implemented in the systematic review (Study Two), namely, the VIO and the injury surveillance system (ISS), provided evidence for an association between the implementation of the VIO model and a reduction in homicide count in high-violence settings (incidence rate ratio [IRR]=0.06; 95% CI 0.02 to 0.19; four studies), while the introduction of ISS showed significant results in reducing assault (IRR=0.80; 95% CI 0.71 to 0.91; three studies). Following expert consultation through a Delphi process (Study Three), this study identified 14 violence and injury indicators and 12 violence-related datasets for inclusion in the pilot VIO. Additionally, research priorities within 16 research themes across five different types of violence were identified including: elder abuse, youth violence, intimate partner violence, sexual violence, and armed violence. Key findings from these thematic priorities included: (1) formal methods to define and measure violence, identification of violence-related risk factors; (2) evaluation of the effectiveness of promising programmes that target violence-related risk factors; and (3) evidence-based recommendations on scaling up programmes that were shown to be effective in reducing interpersonal violence. With regard to the key findings around data sharing, the majority of the panelists (>55%) thought that: (1) violence-related data from health services should be shared with Policing Services; (2) the data model employed should go beyond the Cardiff model (policing and health data) and also include violence-related data from the Fire and Rescue Services (FARS) and the Emergency Medical Services (EMS); and (3) the functions of a local observatory should include a civilian spatial data observatory, an information technology division, a predictive analytics division, a historical data repository and a systematic review repository. The expert-identified violence and injury indicators, datasets and research priorities provide a research framework for interpersonal violence and injury prevention work within South Africa. The findings have theoretical implications and build up evidence-based data for the general field, and they have a practical outcome in recommendations that are both general and specific for implementation in South Africa. They may also serve to guide the development of additional VIOs locally. In the final study (Study Four), with regard to concordance between the datasets, among the 708 patients being treated for violence-related injuries at health facilities, only 104 reported the incident to the police which equates to a matching ratio of 14.7%. Combining health and police data revealed an 81.7% increase in potential total violent crimes over the reporting period. Compared to incidents reported to the police, those not reported were more likely to involve male patients (difference: +47.0%; p< 0.001), and sharp object injuries (difference: +24.7%; p< 0.001) and less likely to report blunt trauma i.e., push/kick/punch injuries (difference: -17.5%; p< 0.001). These findings suggest that the majority of injuries arising from interpersonal violence presenting at health facilities in Khayelitsha are not reported to the police. Conclusion This research provides an evidence-based model for the development and implementation of a VIO, and the Cardiff model, to reduce interpersonal violence. It is supported by the evidence from the systematic review of the effectiveness of VIOs in reducing violence outcomes among adults in high-violence settings. This pilot VIO represents the first attempt to collect contemporary and comprehensive data on violence and injury in the Western Cape Province and South Africa. The implementation of VIOs should be considered in high-violence communities where the collation and integration of violence-related data and violence stakeholders, may guide violence reduction. The Delphi study provided indicators, datasets and research priorities to (1) inform the basic research infrastructure of a VIO, and (2) serve as part of a regional standardised data collection framework to guide the development of other local violence and injury observatories. This is consistent with the aims of the South African National Development Plan 2030 to ‘improve the health information system; to prevent and reduce the disease burden and promote health and to improve quality by using evidence'. Finally, the research further shows a clear benefit in combining data on violence from different settings as demonstrated in our analysis of data in the Cape Town suburb of Khayelitsha, where the overwhelming majority of injuries arising from interpersonal violence presenting at health facilities in Khayelitsha are not reported to the police. This study has broader implications regionally and nationally for the surveillance of injuries arising from interpersonal violence, for the police definition and surveillance of community interpersonal violence, for community policing intelligence development (improving the configuration of violence heat maps on a real time basis) and finally for police resource utilisation and distribution, which should, in turn, impact positively on reducing crime and violence in the community, and reduce the burden on the health services. The Western Cape Safety Plan, a policy document developed by the Western Cape Government, advocates the use of data and technology to understand violent crime patterns to inform the deployment of law enforcement resources and investigators accordingly and furthermore acknowledges research and analysis as an important component of its evidence-based policing (EBP) strategy. The policy document and study findings provide support to the implementation of the Cardiff Model locally.